An International survey on diagnostic and prognostic protocols in patients with disorder of consciousness. (3rd July 2019) - Formisano, Rita; Giustini, Marco; Aloisi, Marta; Contrada, Marianna; Schnakers, Caroline; Zasler, Nathan; Estraneo, Anna
ABSTRACT: To date, no international guidelines or recommendations for diagnosis or prognosis of patients with disorders of consciousness (DoC) have been established. The International Brain Injury Association's (IBIA) Special Interest Group on Disorders of Consciousness (DoC-SIG) launched an international multicenter survey to compare diagnostic and prognostic procedures across countries and clinical settings. Objectives : To explore which specific diagnostic protocols and prognostic indices were utilized in the care for persons with DoC in different countries and to determine the usage, if any, of national guidelines in the care of such patients. Methods : The questionnaire included 17 questions in two distinct sections (I – clinical and instrumental tools and involvement of caregivers and II – clinical, anamnestic and instrumental markers). Results : Physicians composed 50% of the survey respondents (120) and were all involved in post-acute rehabilitation care. In the majority of countries, respondents reported that there were no national guidelines or recommendations for DoC care. The Glasgow Coma Scale (GCS) and the Coma Recovery Scale-Revised (CRS-R) were the most frequently used clinical scales for diagnostic purposes. The majority of respondents reported the involvement of caregivers in the evaluation of behavioral responsiveness of patient with DoC. The survey indicated that only a few centers performed neurophysiological investigations routinely as diagnostic instrumental procedures. Our results suggest that international guidelines and recommendations for the care of persons with DoC still need to be formulated and ideally agreed to by consensus.